2012
DOI: 10.1002/jnm.1834
|View full text |Cite
|
Sign up to set email alerts
|

Calderón preconditioning approaches for PMCHWT formulations for Maxwell's equations

Abstract: Preconditioning methods based on Calderón's formulae for the Poggio-Miller-Chang-Harrington-Wu-Tsai formulations for Maxwell's equations in 3D are discussed. Five different types of formulations are proposed. The first three use different basis functions for surface electric and magnetic currents. The first type is a preconditioning just by appropriately ordering the coefficient matrix using the Gramian matrix as the preconditioner. Other two types utilise preconditioners constructed using matrices needed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, if the quadrilateral is exactly a parallelogram, then the surface divergence is independent of the parameters . It is also found that (23) which indicates that the integration of the divergence of , viz., total surface charge on , is 4, independent of its shape or size. The factor 4 is rooted in the fact that the parameter space has an area of 4.…”
Section: B Parameterized Quadrilateralsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, if the quadrilateral is exactly a parallelogram, then the surface divergence is independent of the parameters . It is also found that (23) which indicates that the integration of the divergence of , viz., total surface charge on , is 4, independent of its shape or size. The factor 4 is rooted in the fact that the parameter space has an area of 4.…”
Section: B Parameterized Quadrilateralsmentioning
confidence: 90%
“…Interlocking mesh method [8] was an attempt in defining DBFs for (curvilinear) quadrilaterals. Rooftop BFs were investigated for rectangles [23]. However, these approaches have mesh restrictions and are not general.…”
Section: Introductionmentioning
confidence: 99%
“…Squaring the operator in this way regularizes the system by shifting the accumulation points of the spectrum away from the origin and taming the hypersingular component. For details we refer to [51,50,52], but the regularization relies on the following relations (contained in (30)-(31)):…”
Section: Galerkin Methods and Preconditioningmentioning
confidence: 99%
“…In particular we note that in the Bempp implementation, the BC basic functions are ordered and rotated consistently with their RWG siblings. But we note that other discretizations are possible [50,52] and are just as easily implemented with the Bempp software package.…”
Section: Galerkin Methods and Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation